Cobalt(III) Complexes of D‐Galactosylamine1. Issue 11 (14th July 2015) - Lindner, Leonie; Klüfers, Peter
Abstract The β‐pyranose isomer of D‐galactosylamine (1) formed complexes with three different cobalt(III) fragments. Crystals containing the dication [Co(tren)(β‐D‐Galp1N2H–1‐κ2N1, O2)]2+ (3) showed coordination through the anomeric amino group (N1) and the deprotonated hydroxy group (O2) of the 4C1 β‐pyranose form, which is also the major isomer of free galactosylamine. The cationic complexes [Co(fac‐dien)(β‐D‐Galp1N2H–1‐κ2N1, O2)]2+ (4) and [Co(phen)2(β‐D‐Galp1N2H–1‐κ2N1, O2)]2+ (5) were analysed by NMR spectroscopy and showed the same coordination mode as 3. In terms of available ligand isomers it was shown that 1 exhibits an anomeric equilibrium in solution of both pyranose and both furanose forms as is typical for the parent glycose, galactose.